Avaliação de diferentes sistemas de alimentação sobre as características que afetam a qualidade da carcaça e da carne - Menezes, Luis Fernando Glasenapp de (2008)
This work was divided in two experiments. In first the objective was to evaluate the carcass, meat, carcass no integrants components and fatty acids profile of intramuscular fat of Devon steers finished in: feedlot (CONF), or winter pasture (pasture of ryegrass - Lolium multiflorum Lam -PTEM), or tropical pasture (association of millet pasture - Pennisetum americanum (L.) Leeke and alexander grass Brachiaria plantaginea - PTRO). At the beginning of finishing the average weight of steers was 320 kg and age was 15 months. The roughage:concentrate ratio from CONF was 60:40. The finishing in feedlot and winter pasture showed lower slaughter age in relation to finishing in tropical pasture, resulting in carcass of better quality. The animals finished in winter pasture showed meat more black and lower tenderness in relation to CONF or PTRO. However, the PTRO animals showed lower palatability. The feeding system affect the carcass no integrants components, principally the absolute and relative of liver, total weight of all internal organs, rumen-reticulum, heart fat and intestines fat that were higher from PTEM. The absolute and relative weight of blood and omasum were higher from CONF. The tract gastrointestinal content weight was higher from PTRO. Theses differences must be taken into account when calculating nutrition requirements for animals in finishing. The finishing in winter pasture show meat with intramuscular fat more beneficial in comparison to finishing in feedlot, principally by higher contents of CLA, ω-3 total and lower ω-6/ω-3 ratio. The finishing in tropical pasture resulted in meat with nutritional values intermediaries to PTEM and CONF. In the second experiment the objective was to evaluate the changes of fatty acids profile intake and duodenal digest of steers fed with diets different: Conventional = diet typical of feedlot (60% of maize silage and 40% of concentrate); winter pasture silage (pasture of ryegrass - Lolium multiflorum Lam), or tropical pasture silage (association of millet pasture - Pennisetum americanum (L.) Leeke and alexander grass Brachiaria plantaginea). Six steers crossbreds Charolais x Nellore with cannulas in duodenum were used, in a 3 x 3 double Latin square design. The conventional diet show higher changes of fatty acids profile intake to fatty acids profile duodenal digest, principally in saturated and polyunsaturated fatty acids. The presence de concentrated in diet stimulated production of vacenic acid in duodenal digest, however inhibited the production of CLA